Evaluation of truck driver rest locations and sleep quality - Rocha, Felipe Pereira; Marqueze, Elaine Cristina; Kecklund, Göran; Moreno, Claudia Roberta de Castro (Sleep Science, 2022)
Objectives: Truck drivers’ work organization requires that rest and sleep be taken in various locations, where sleep quality might be affected by the discomfort of these environments. The purpose of this study was to evaluate truck drivers’ rest locations and their association with sleep quality utilizing an ergonomic approach.Material and Methods: The sleep quality of 81 truck drivers was assessed using the Pittsburgh sleep quality index (PSQI). An adapted version of the ergonomics workplace analysis (EWA) instrument was used to evaluate 44 rest locations.Results: Half of the workers preferred sleeper berths (51.2%) as a rest place. Sleep was classified as poor by 71.6% of the drivers. Dorms were rated more positively (p<0.001) by truck drivers (2.0±1.1) than by the analyst (2.6±0.6). Sleeper berths and dorms were rated statistically different by truck drivers (p=0.002), as well as by the analyst (p=0.003). No correlation was found between EWA evaluations and total score for sleep quality. Separate analyses of dorms and truck berths showed very few correlations. The higher the noise of roommates in dorms, the worse the sleep quality. Conversely, noise in corridors or outside the room positively impacted sleep quality.Conclusion: Noise in the rest place may affect sleep in both directions, negatively or positively. Sleep was classified as poor regardless of resting place. The quality of resting places seemed to have little effect on sleep quality of truck drivers. Factors other than rest place, such as work scheduling, are probably more important for promoting good sleep quality.
Keywords: Sleep; Resting Places; Truck Drivers; Public Health